2021
DOI: 10.1016/j.ijdrr.2021.102188
|View full text |Cite
|
Sign up to set email alerts
|

Psychological effects of the COVID-19 outbreak on nurses working in tertiary women's and children's hospitals from Sichuan, China: A cross-sectional study

Abstract: The evolving COVID-19 pandemic is placing unprecedented pressures on health systems. Accumulative studies suggest that nurses were more likely to develop negative psychiatric outcomes following a public health disaster than other medical staffs, due to their more frequent and closer contact with patients. We examined the psychological status of nurses working in the tertiary women’s and children’s hospitals in Sichuan, China, in order to explore the possible effect of the COVID-19. The cross-sectional survey w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…This may be related to differences in gender traits. Women are more concerned about inner experiences and self-perceptions, which makes them more fragile and sensitive, and more prone to anxiety (He et al, 2021). Agree with the results of this study, research in ICU nurses shows that female ICU nurses tend to experience severe anxiety (Heesakkers, Zegers, van Mol, & van den Boogaard, 2021).…”
Section: Discussionsupporting
confidence: 55%
“…This may be related to differences in gender traits. Women are more concerned about inner experiences and self-perceptions, which makes them more fragile and sensitive, and more prone to anxiety (He et al, 2021). Agree with the results of this study, research in ICU nurses shows that female ICU nurses tend to experience severe anxiety (Heesakkers, Zegers, van Mol, & van den Boogaard, 2021).…”
Section: Discussionsupporting
confidence: 55%
“…A greater prevalence of anxiety was found in frontline healthcare responders compared to second-line or non-COVID-19 healthcare workers, and this was highlighted in twelve papers [ 29 , 30 , 34 , 43 , 48 , 51 , 53 , 69 , 74 , 76 , 109 , 113 ]. This was further endorsed, as healthcare staff not working in COVID-19 epicentres scored lower for anxiety [ 57 ]. Amongst clinical healthcare workers, more studies found that nurses suffered to a greater level from anxiety than physicians [ 53 , 69 , 73 , 95 ].…”
Section: Resultsmentioning
confidence: 99%
“… Chen et al, 2021 ), ( Cheng et al, 2021 ), ( Fang et al, 2021 ), ( Kang et al, 2021 ), ( Khoury et al, 2021 ), ( Lan et al, 2021 ), (Y an Liu et al, 2021 ), (Yu an Liu et al, 2021 ), ( Liu et al, 2020 ), ( Mistry et al, 2021 ), ( Nkire et al, 2021 ), ( Veldhuis et al, 2021 ), ( Wang et al, 2021 ) Lack of social support / community support 10 3.95 (Feng et al, 2021), ( Glenister et al, 2021 ), ( Hong et al, 2021 ), ( Kang et al, 2021 ), ( Khoury et al, 2021 ), (Yu an Liu et al, 2021 ), ( Nkire et al, 2021 ), ( Sun et al, 2021 ), ( Wang Liu et al, 2021 ), (H. Wang et al, 2021 ) Geographical location of cohort 10 3.95 ( Ganson et al, 2021 ), ( Glenister et al, 2021 ), ( Guo et al, 2021 ), ( Rashid et al, 2021 ), ( Kim et al, 2021 ), ( Rossell et al, 2021 ), ( Wu et al, 2021a ), ( Yan et al, 2021 ), ( Yasmin et al, 2021 ), (Yunus et al, 2021) Increase workload/ workload changes / working conditions 9 3.56 (J. Chen et al, 2021 ), ( Crowe et al, 2021 ), ( Fang et al, 2021 ), ( Hammond et al, 2021 ), ( He et al, 2021 ), ( Li et al, 2021 ), (Y. Liu et al, 2021 ), ( Parthasarathy et al, 2021 ), ( ...…”
Section: Resultsmentioning
confidence: 99%
“… Liu et al, 2021 ), ( Wang Liu et al, 2021 ) Lack of education/awareness towards COVID 5 1.98 ( Cheema et al, 2021 ), ( Cheng et al, 2021 ), ( Faisal et al, 2021 ), ( Hazarika et al, 2021 ), ( Yang et al, 2021 ) Being HCW 4 1.58 (Huang et al, 2021), ( Kar et al, 2021 ), ( Liu et al, 2021 ), ( Matsumoto et al, 2021 ) Job burnout 4 1.58 (J. Chen et al, 2021 ), ( He et al, 2021 ), ( Rashid et al, 2021 ), ( Young et al, 2021 ) Others 21 8.32 ( An et al, 2021 ) (Yu an Liu et al, 2021 ), ( Robillard et al, 2021 ), ( Suzuki et al, 2021 ), ( Cheema et al, 2021 ), ( Glenister et al, 2021 ), ( Nishimura et al, 2021 ), ( Devkota et al, 2021 ), (Y. Liu et al, 2021 ), ( Matsumoto et al, 2021 ), ( Gotlib et al, 2021 ), ( Wolfson et al, 2021 ), Lietal 2021a, ( Nomura et al, 2021 ), ( Perera et al, 2021 ), (S. Sun et al, 2021 ), ( Moore et al, 2021 ) …”
Section: Resultsmentioning
confidence: 99%